ANALISIS INFLASI DAN TINGKAT PENGANGGURAN DI SUMATERA BARAT TAHUN 1991-2013 - Octaviani, Era; Maryati, Sri; Eka Putri, Yosi (Pendidikan Ekonomi, 2014)
ABSTRACTÂ The purposes of this research is to identify the correlation of inflation and unemployment or the correlation of unemployment and inflation and to identify whether the Phillipâs Curve could be implemented in West Sumatera. This is quantitative research with secondary data. The secondary data that used is CPI (Consumen Price Index) annual report to see the inflation and unemployment rate in West Sumatera between 1991 â 2013 with Stationarity and Ganger Causality as the tools to measure the rate. The result of this research shows that inflation has the stationarity wether it is with trend, trend and intercept, also without trend and intercept. Unemployment variabel shows that it is stationary wether it with trend or without trend and intercept. While the ganger causality test shows that there is no correlation between inflation and unemployment. It also proves that there is no correlation between unemployment and inflation. In this research, writer also found that inflation has positive correlation and significant towards the unemployment in West Sumatera which is can be shown with the coefficient 5.556806 and t-statistic 2.330654, the probability 0.0298, RÂ2=0.205507 or 0,20%. The positive value of the inflation variabel proves that the Phillipâs Curve Theory can not be implemented in West Sumatera.